Caracterização e correlações ópticas, cristaloquímicas e espectroscópicas de gemas do município de Quixeramobim, CE, Brasil - Oliveira, Isaac Gomes de (2024)
This study aimed at the gemological characterization of some mineral specimens such as tourmaline, aquamarine, garnet, and amethyst from the Quixeramobim region (CE); in addition to gemological quality; commercial value; analysis using the patented instrument, Gomes polariscope (Constructive Arrangement Introduced in Polariscope for Gem Study and Analysis); data on their chemical composition; crystal-chemical structure; spectroscopic and optical data. For the study of these four gemological minerals, classical gem characterization equipment was used, with the addition of the Gomes polariscope, the “Diamond and Colored Gemstones Price Reference Bulletin,” and a table of 384 colors; as well as the use of the scanning electron microscope (SEM-EDS); Raman spectroscope; single-crystal X-ray diffraction (XRD); and petrographic microscope. The municipality of Quixeramobim has 6 colors of tourmaline (blue, green, pink, red, blue with green, and pink with green), all the elbaite species; the region also has two groups of garnets, grossular and spessartine. The tourmalines, aquamarines, and garnets from the municipality of Quixeramobim have gemological quality and mostly the same characteristics as minerals from other regions, however, they exhibit notable and linear correlations; in addition to some variations, peculiarities, and anomalies in certain properties. The correlations, peculiarities, and anomalies of the mentioned minerals involve: color; refractive index; birefringence; density; pleochroism; fluorescence; quality of interference figures; interference mosaic; as well as the amounts of FeO, NiO, Na2O, CaO, Mn2O3, and PbO2; also including unit cell dimension and volume; molecular weight, and Raman bands. The amethysts from the Quixeramobim region have gemological quality and essentially the same characteristics as amethysts from other regions of Brazil and the world; unlike the other minerals listed above, this quartz has no correlations or peculiarities, except for a notable amount of Al2O3 in its structure. Therefore, through the listed instruments and accurate analyses, it was possible to perform the optical/gemological, crystal-chemical, and spectroscopic characterization. Thus, this research provides a compilation of the data on these minerals in this municipality in Brazil, proving that the gems from the municipality of Quixeramobim are unique. The notable correlations in these gems are not restricted to a single mineral but are related to other minerals in the region, functioning as a mineral signature; this study also has the quality of mineral provenance for these specimens. The correlations, peculiarities, and anomalies present in tourmalines, aquamarines, and garnets (especially grossular) make these gems unique not only on a national scale but possibly on a global scale